2019
DOI: 10.1002/joe.21949
|View full text |Cite
|
Sign up to set email alerts
|

What makes employees want to stay? A study in the Malaysian manufacturing sector

Abstract: An organization's employee retention rate can signal a source of competitive advantage or risk. Yet, many of the factors that can affect retention rates have not been adequately studied, particularly in sectors where competition for highly qualified employees is fierce, such as the Malaysian manufacturing industry. To assess the impact of three categories of organizational initiatives—performance management, rewards and recognition, and hiring and promotion practices—on employee retention in Malaysia, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…Organization's performance management policies, including unbiased appraisal and equal opportunities to growth, help employees to increase their productivity and their intention to remain (Biron & Boon, 2013). Positive perception towards the organizational performance and career management system can be a predictor of retention intentions (Subramaniam et al, 2019).…”
Section: Performance and Career Managementmentioning
confidence: 99%
“…Organization's performance management policies, including unbiased appraisal and equal opportunities to growth, help employees to increase their productivity and their intention to remain (Biron & Boon, 2013). Positive perception towards the organizational performance and career management system can be a predictor of retention intentions (Subramaniam et al, 2019).…”
Section: Performance and Career Managementmentioning
confidence: 99%
“…Jackson et al (2012) further asserted that rewarding of high performers by leaders encourages and uphold their performance levels and hard work; recognition given towards any tasks may further motivate an employee to double more efforts to accomplish the tasks. As refer to research done by Subraminiam et al (2019), employee recognition had a significant impact on employees' willingness to remain with their employer. Also, in Wong et al ( 2020) study, they discovered that to lower the turnover rate of nurses, it is important of having a good leadership strategy towards nurses by recognizing their contribution as an organization's "asset" or valuables to improve their satisfaction and well-being.…”
Section: Work-life Balancementioning
confidence: 99%
“…However, very little scholarly research on TM practices and retention among engineers has been implemented (Nittala & Jesiek, 2018;Van Hoek & Schultz, 2013). Furthermore, very little research on TM practices and retention has been found in the manufacturing sector (Osman et al, 2017(Osman et al, , 2018Subramaniam et al, 2019). Most of the previous findings were found from sector of construction (Shikweni et al, 2019); education (Zeeshan, 2020); ICT (Ahmed & Yang, 2017); GLCs (Government-linked Companies) (Isa et al, 2018); private organisations (Singh & Sharma, 2015); hospital (Eltaybani et al, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
“…The specific aspects of the manufacturing working environment in Malaysia are likely to affect engineers' retention. It follows, then, that training and development and various aspects of the work environment must be given serious attention to address engineer retention issues in the manufacturing sector (Subramaniam et al, 2019). Engineers in developed countries consider manufacturing engineering work and infrastructure always needs expansion and development.…”
Section: Intention To Stay Among Manufacturing Engineersmentioning
confidence: 99%
See 1 more Smart Citation